Settlement ecology of the ancient Americas
1 online resource (xi, 319 pages)
Keywords: "How did ancient societies of the Americas decide where to settle on the landscape? What were the specific social, cultural and environmental factors which mediated the placement and arrangement of different kinds of sites? In this volume, leading researchers address these questions by utilizing a settlement ecology approach for understanding the spatial arrangement of prehistoric settlement patterns across the Americas"--Provided by publisher.